Postharvest treatments and maturity stages impact sensory attributes and shelf life of tomato fruits var. Pearson kept in Zero Energy Cool Chamber - Samiullah Hakimi, Sayed; Raina, Ravinder; Saharawat, Yashpal Singh (Emirates Journal of Food and Agriculture, 2022)
The investigation has been carried out under ZECC conditions located at the research farm of agriculture faculty of Kabul University, Afghanistan. The objective was to understand the effect of postharvest treatments and harvesting stages on the shelf life and sensory quality of tomato fruits. It was found that both main factors had a significant effect and the highest shelf life noted for the fruits of H1 (turning color stage) and D1 (dipped in 6 % CaCl2 solution) was 26.19 and 25.17 days, respectively. At the end of the storage period, the final evaluation average scores for overall sensory attributes of turning color fruits were higher whereas it was noted lower for light red color fruits compared with initial scores. The highest scores for all attributes such as color, flesh texture, flavor, and overall acceptance were noted for the fruits of H1 and D1 respectively. Thus, the turning color stage has seen as a suitable harvesting stage and then followed by pink color stage of the tomatoes of the Pearson variety that could be considered for various purposes after storage respectively. The 6 % CaCl2 solution could increase tomatoes shelf life and maintain the quality that it had retained the fruits sensory attributes to an acceptable level